Restorative Justice and Family Violence : Peacemaking - Pennell, Joan (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
By engaging families in taking charge of their affairs, restorative justice can reverse family violence. But the expansion of restorative programming into family violence is stymied by fears of setting family members at risk and heightening agency liability if harm results. How does this anthology counter these fears? In response, it provides two decades of studies documenting successes of a restorative approach with gendered and intergenerational violence. It offers feminist frameworks to explain how these successes are achieved. And finally, the author turns to cultural and religious messages from her own upbringing as a Quaker (Religious Society of Friends) to explain why a restorative approach makes lasting and just peace in homes. The aim is to encourage others to identify such principles in their own backgrounds to safely and confidently expand the use of restorative programming to safeguard children and adults in the home.